Isolated pulmonary cavitary mucormycosis in uncontrolled diabetic, diagnosed by fiber-optic bronchoscopy and completely managed medically - Waseem, MD. Abdul; Zahera, Misba; V., Gopalakrishnaiah (International Journal of Research in Medical Sciences, 2017)
Pulmonary mucormycosis is rare life‐threatening infection affecting mostly immunocompromised individuals such as diabetes mellitus, hematological malignancies, chronic renal failure, post transplantation etc. Based on the anatomic site involved, mucormycosis can be one of several forms, such as rhinocerebral, pulmonary, cutaneous, gastrointestinal, disseminated, and uncommon presentations that include endocarditis, osteomyelitis, peritonitis, and renal infection. Pulmonary infection is the most common form of mucormycosis recognized in patients with hematological malignancy and remains the second most common presentation after rhinocerebral infection in diabetic patients. Its presentation in the lungs may mimic cavitary diseases like tuberculosis, mass lesions as in malignancies and non-resolving pneumonias. Here we report a case of isolated pulmonary mucormycosis in an uncontrolled diabetic male patient with a cavitary lesion. Diagnosis was made with a bronchoscopic biopsy and treatment was completely medical with liposomal amphotericin B.